2019
DOI: 10.3390/en13010054
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Bio-Briquette Fuel by Using Spent Coffee Ground as an External Additive

Abstract: The present study investigates the quality changes of wood bio-briquette fuel after the addition of spent coffee ground (SCG) into the initial feedstock materials (sawdust, shavings) in different mass ratios (1:1, 1:3). Analysis of SCGs fuel parameter proved great potential for energy generation by a process of direct combustion. Namely, level of calorific value (GCV = 21.58 MJ·kg −1 ), of ash content (Ac = 1.49%) and elementary composition (C = 55.49%, H = 7.07%, N = 2.38%, O = 33.41%) supports such statement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…The pellets have an excellent level of heating value compare to other types of waste and to other biomasses, a fact that emerges from the comparison made by Zuorro and Lavecchia (2012) between SCG and other agricultural and forestry biomass or waste of which they report HHV, such as forest residues with 21.70 MJ/kg and a percentage variation of 3.04% with the HHV value of SCG obtained in this work, rice husks (15.29 MJ/kg, 46.24%), oak wood (18.70 MJ/kg, 19.57%), olive kernel (20.40 MJ/kg, 9.61%) and others 34 . The literature reports high levels of residual oil, which may be partially responsible for the high heating value 35 .The analysis showed decreasing values of HHV and LHV with increases in the percentage of sawdust. The best results were produced by the treatment without sawdust and the treatment consisting of 15% sawdust (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…The pellets have an excellent level of heating value compare to other types of waste and to other biomasses, a fact that emerges from the comparison made by Zuorro and Lavecchia (2012) between SCG and other agricultural and forestry biomass or waste of which they report HHV, such as forest residues with 21.70 MJ/kg and a percentage variation of 3.04% with the HHV value of SCG obtained in this work, rice husks (15.29 MJ/kg, 46.24%), oak wood (18.70 MJ/kg, 19.57%), olive kernel (20.40 MJ/kg, 9.61%) and others 34 . The literature reports high levels of residual oil, which may be partially responsible for the high heating value 35 .The analysis showed decreasing values of HHV and LHV with increases in the percentage of sawdust. The best results were produced by the treatment without sawdust and the treatment consisting of 15% sawdust (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Although a significant decrease of the mechanical durability index for a larger fraction was observed, the Du values can be considered satisfactory. The research of other authors showed that briquettes made of plant materials should be characterized by the higher mechanical durability index Du, exceeding 80% [42][43][44]. However, these values are not always achieved.…”
Section: The Mechanical Durability Index-pn-en Iso 17831-2: 2016-02 Standardmentioning
confidence: 97%
“…In order to accomplish the requirement for national energy independence and the reduction of fossil fuel consumption, which bring a consequent mitigation of climate change and greenhouse gas emissions, the application of renewable resources for chemical and energy substitution is nowadays very important. Among the technologies based on renewable resources, biomass-based plants have huge commercial potential, owing to the great biomass availability, the possibility of reaching negative greenhouse gas emissions, and having greater impacts on and cross-fertilization with other sectors; however, efficient and reliable low emission technologies still have to be developed [1][2][3][4][5][6][7][8]. Biomass gasification is one of the most practicable applications within biomass-based power plants, allowing achieving a high-rate production of fuel gas, with small investment costs [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%